Philosophical Analysis in Latin America - Gracia, J.J.; Rabossi, E.; Villanueva, Enriq; Dascal, Marcelo; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 1984)
Historians of Latin American philosophy have paid relatively little attention to the development of philosophical analysis in Latin America. There are two reasons for this neglect: First, they have been primarily concerned with the forma tive period of philosophical development, in particular with the so called "founders" of La ti n American philosophy. And second. philosophical analysis did not become a noticeable philosophical trend in Latin America until recent years. True. a nunber of Latin American philosophers took notice of Moore. Russell. the members of the Vienna Circle and other important figures in the analytic movement qui te early. But these were isolated instances that lacked the sustained effort and broad base indispensible to make a serious impact in the development of Latin American philosophy. That has changed now. There are not only good numbers of philosophers who work within the analytic tradition, but also some journals and institutes dedicated to the analytic mode of philosophizing. It is. therefore. most appropriate to publish a collection of articles which would introduce the reader of philosophy to the most representative analytic material produced so far in Latin America. Indeed. it is not only appropriate. but also necessary. since most of the published analytic literature to date is scattered in various journals, sometimes of difficult access. Moreover, not all that has been published is representative of the best already produced and of the potential that the movement has in Latin America.
I. Philosophical Analysis in Argentina -- I. Philosophical Analysis in Argentina -- Normative Knowledge and Truth -- Legal Principles and Legal Positivism -- Logic and the Hypothetical-Deductive Method -- The Limits of the Enforcement of Morality Through the Criminal Law -- On the Inconsistency of Meinong$1 (Bs Ontology -- Meaning, Force and Explicit Performatives -- II. Philosophical Analysis in Mexico -- II. Philosophical Analysis in Mexico -- Existential Quantifiers and Guiding Principles in Physical Theories -- (Simple) Qualities and Resemblance -- Theory of Descriptions, Meaning and Presupposition -- Ethics and the Language of Morality -- The Private Language Argument -- III. Philosophical Analysis in Brazil -- III. Philosophical Analysis in Brazil -- Philosophy, Common Sense, and Science -- Decidability and Cognitive Significance in Carnap -- Natural Conjectures -- IV. Philosophical Analysis in Other Latin American Countries -- IV. Philosophical Analysis in Other Latin American Countries -- Popper$1 (Bs Solution to the Problem of Induction -- On the Concept of Reason -- Appendix: Latin Americans Residing in the United States and Canada / Jorge J. E. Gracia -- Biographical Notes -- Index of Proper Names.s
Keywords: Philosophy and science; Philosophy of Science